The effectiveness of the SSCS educational model in improving the reflective thinking in mathematics for tenth grade students - Al Jarrah, Ebtessam Awni; Al Zoubi, Ali Mohammed (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed to identify the effectiveness of the SSCS educational model in improving the reflective thinking in mathematics among tenth grade students. Methods: The study used a quasi-experimental approach with pre- and post-measurements. The study sample consisted of 40 students who were equally distributed between the control and experimental study groups. To achieve the study objectives, a reflective thinking test was developed, consisting of five skills: meditation and analysis, fallacy detection, conclusion drawing, persuasive explanation, and proposed solution development. The reliability and validity of the test were also verified. Result: The results of study showed that there were statistically significant differences between the averages for the performance of students of the experimental and control groups on each skills on reflective thinking in mathematics individually, as well as for the overall reflective thinking test in mathematics. These differences were attributed to the teaching method and favored the experimental group. Conclusions: Based on the study results, the researchers recommend the necessity of employing the SSCS educational model in teaching mathematics to tenth grade students.